Pengaruh Pemahaman Akuntansi dan Ketentuan Perpajakan, Sanksi Pajak serta Pemanfaatan Teknologi Informasi terhadap Kepatuhan Wajib Pajak UMUM di Kota Kupang - Fransiskus Marlon Reu; Ferayani Besa; Martina Kaisrani Rupa (Jurnal Inovasi Akuntansi (JIA), 2023)
This research was conducted to determine the factors that influence the level of compliance of MSME taxpayers using the variables understanding accounting, understanding tax provisions, tax sanctions, and the use of information technology. This research uses quantitative data, the data used in this research is primary data and secondary data. The data collection technique uses a questionnaire containing statement items for each variable studied using a Likert scale. The data analysis technique used in this research is descriptive statistics by measuring using the SPSS 29 application. The research was carried out in Kupang City. Based on the results of the research conducted, it can be concluded that the level of compliance of MSME taxpayers in the city of Kupang is still categorized as very low, and the factors that can influence the level of compliance of MSME taxpayers are the variable understanding of tax provisions and tax sanctions which have a significant influence. The variables Understanding accounting and use of information technology do not significantly influence the level of MSME taxpayer compliance.